TARI TRADISI GAYA SURAKARTA - Sriyadi Sriyadi (Institut Seni Indonesia Surakarta, 2013)
Traditional Surakarta style dance is a cultural heritage that must not be changed. It hasbeen passed down over many generations as a legacy that still adheres to the rules and regulationsthat were first determined by early dancers. The presence of Surakarta style dance in the royalpalace is an example of an important cultural heirloom that belongs to the king and is also aconcept for the kingâ€™s power or legitimacy.Â